(untitled) (Research, Society and Development, 2021)
Medications are important health tools, but their administration must be performed with caution, evaluating the benefit/risk ratio and effectiveness for the clinical indication for which they are intended. The effects of the drug clonazepam when associated with the use of alcohol is harmful to health, causing the dose to change and enhancing its effects. When this interaction happens, the individual tends to suffer the consequences, which are usually serious. As a result, this article seeks to highlight the drug interaction of clonazepam and alcohol, demonstrating how the use of both together affects the SNC (Central Nervous System). The article will have four parts, in the first part we will talk about what clonazepam is, in the second part we will show what happens when ingested with alcohol, in the third part we will present a discussion on the subject and finally the results/conclusions.